The Influence Of Service Quality, Service Facilities, Discipline Of Service Officers, Service Procedures, Interpersonal Communication And The Ability Of Service Officers On Satisfaction In The Community Of Tanjung Enim Selatan Sub-District. Lawang Kidul D - Medaryani Medaryani; Abdul Hamid; Darmin Darmin (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this study was to determine and analyze the influence of service quality, service facilities, discipline of service officers, service procedures, interpersonal communication and the ability of service officers both individually and collectively on satisfaction in the people of South Tanjung Enim Village, Lawang Kidul District, Regency Muara Enim. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results of the study obtained that service quality has a significant effect on satisfaction in the people of South Tanjung Enim Village, Lawang Kidul District, Muara Enim Regency. Service facilities have a significant effect on community satisfaction. Discipline of service personnel has a significant effect on community satisfaction. Service procedures have a significant effect on community satisfaction. Interpersonal communication has a significant effect on community satisfaction. The ability of service officers has a significant effect on community satisfaction. Service quality, service facilities, discipline of service personnel, service procedures, interpersonal communication and the ability of service personnel have a significant effect on satisfaction of the people of Tanjung Enim Selatan Village, Lawang Kidul District, Muara Enim Regency.